Words to Documentary Editors - Shu Voon, Ding; Chong Lee, Yow (Mini Film Festival, 2022)
Infographics on "Words to Documentary Editors". The content is extracted from MFF Doc Workshop (3) presented by Mr. Yosep Anggi Noen, designed by Shu Voon, advised and edited by Yow.